Agile Leadership and Knowledge Sharing In Improving Lecturer Performance - Wawan Ruswandi; Rosanna Wulandari; Dewi Resmanasari; Riki Riswandi; Ce Mulya Rizki Anugrah (Dinasti International Journal of Education Management And Social Science, 2024)
This research aims to investigate the role of Agile Leadership and knowledge-sharing practices on lecturer performance in higher education institutions. The quantitative method of multiple regression analysis was used to collect and analyze data from questionnaires distributed to lecturers at Linggabuana PGRI Sukabumi University, with a sample of 72 permanent foundation lecturers. The results of the analysis show that Agile Leadership and knowledge sharing simultaneously have a tremendous influence on lecturer performance. Agile Leadership makes an extraordinarily positive contribution to lecturer performance while knowledge-sharing practices also have a positive and extraordinary impact. These findings emphasize the importance of implementing Agile Leadership principles and encouraging knowledge-sharing practices as a strategy to improve lecturer performance in higher education environments. The practical implication of these findings is the need for educational institutions to develop a culture of responsive leadership and encourage collaboration and exchange of knowledge between lecturers to increase the effectiveness of teaching, research, and community service.